Analysis of laterally loaded piles in soft clay considering scour-hole dimensions. (1st January 2016) - Lin, Cheng; Han, Jie; Bennett, Caroline; Parsons, Robert L.
Abstract: Scour is a process of soil erosion around foundations, resulting in a reduced capacity of the foundations or even failure of the structures. When there are isolated foundations in the midst of water currents, scour holes are formed around the foundations. In practice, scour effects on the foundations are evaluated or designed by ignoring the scour-hole geometry. Instead, scour effects are considered by simply removing the whole soil layer to the scour depth. However, scour-hole dimensions include not only scour depth but also scour-hole width and slope angle. To date, the widely used p – y method for analyzing laterally loaded piles cannot consider three-dimensional scour-hole dimensions. For this reason, a simplified method was developed in this study for the analysis of laterally-loaded piles in soft clay under scour conditions by modifying the p – y curves. The simplified method was used to evaluate the effects of scour-hole dimensions on responses of laterally loaded piles in soft clay. The computed results were compared with those from the 3D finite difference method. The analysis indicated that ignoring the scour-hole dimensions could result in 10–19% larger lateral pile-head displacements and 6–8% larger bending moments than what would be computed while considering them. Highlights: Three-dimensional numerical models were developed to analyze laterally loaded piles in scoured holes in clay. A simplified solution was proposed to analyze laterally loaded piles in scoured holes in clay. The effects of scour-hole dimensions, including scour depth, width, and slope angle, on the performance of lateralled loaded pipes were examined. Scour depth had the most significant effect on the pile performance.